Depletion of the FtsH1/3 Proteolytic Complex Suppresses the Nutrient Stress Response in the Cyanobacterium Synechocystis sp strain PCC 6803. Issue 12 (15th October 2019) - Krynická, Vendula; Georg, Jens; Jackson, Philip J.; Dickman, Mark J.; Hunter, C. Neil; Futschik, Matthias E.; Hess, Wolfgang R.; Komenda, Josef
Abstract : The FtsH1/3 protease complex is critical for acclimation of the model cyanobacterium Synechocystis to nutrient stress, specifically iron, phosphate, carbon, and nitrogen starvation. Abstract: The membrane-embedded FtsH proteases found in bacteria, chloroplasts, and mitochondria are involved in diverse cellular processes including protein quality control and regulation. The genome of the model cyanobacterium Synechocystis sp PCC 6803 encodes four FtsH homologs designated FtsH1 to FtsH4. The FtsH3 homolog is present in two hetero-oligomeric complexes: FtsH2/3, which is responsible for photosystem II quality control, and the essential FtsH1/3 complex, which helps maintain Fe homeostasis by regulating the level of the transcription factor Fur. To gain a more comprehensive insight into the physiological roles of FtsH hetero-complexes, we performed genome-wide expression profiling and global proteomic analyses of Synechocystis mutants conditionally depleted of FtsH3 or FtsH1 grown under various nutrient conditions. We show that the lack of FtsH1/3 leads to a drastic reduction in the transcriptional response to nutrient stress of not only Fur but also the Pho, NdhR, and NtcA regulons. In addition, this effect is accompanied by the accumulation of the respective transcription factors. Thus, the FtsH1/3 complex is of critical importance for acclimation to iron, phosphate, carbon, and nitrogen starvation in Synechocystis.